2009
DOI: 10.2174/156720509787602942
|View full text |Cite
|
Sign up to set email alerts
|

GEPT Extract Reduces Aβ Deposition by Regulating the Balance Between Production and Degradation of Aβ in APPV717I Transgenic Mice

Abstract: The combination of GEPT extracts can reduce levels of endogenous Abeta peptide in APPV717I transgenic mice through the inhibition of PS1 activity rather than BACE1 and the promotion of IDE and NEP activity. Lower-expression of PS1 and over-expression of IDE or NEP may be helpful in potentially lowering brain Abeta levels in subjects with AD, and hence GEPT appears to offer potential that should be explored in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
0
28
1
Order By: Relevance
“…In addition, the dosage of Aricept in this study was 0.65 mg/ kg/day, which is much less than other studies (0.92 mg/kg/ Yang et al The improvement of spatial memory deficits in APP/V717I transgenic mice by chronic anti-stroke herb treatment 1015 day). 17,18,32 Furthermore, clinical studies have shown that cognitive effects are better at a higher concentration of Aricept (23 mg/day) compared with a lower concentration (5 mg/day or 10 mg/day). 33 Therefore, we suspect that the lack of effect of Aricept on the early treatment strategy was due to its dosage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dosage of Aricept in this study was 0.65 mg/ kg/day, which is much less than other studies (0.92 mg/kg/ Yang et al The improvement of spatial memory deficits in APP/V717I transgenic mice by chronic anti-stroke herb treatment 1015 day). 17,18,32 Furthermore, clinical studies have shown that cognitive effects are better at a higher concentration of Aricept (23 mg/day) compared with a lower concentration (5 mg/day or 10 mg/day). 33 Therefore, we suspect that the lack of effect of Aricept on the early treatment strategy was due to its dosage.…”
Section: Discussionmentioning
confidence: 99%
“…GEPT, a combination of five active components extracted from Chinese herbs, may be valuable for the treatment of AD - reducing the level of Aβ via the inhibition of γ-secretase (presenilin-1) and the promotion of insulin-degrading enzyme and neprilysin, which has been reported in the brain of APPV717I transgenic mice [13]. A 24-week preliminary study of GEPT showed a significant improvement on cognitive function in patients with amnestic mild cognitive impairment, an early stage of AD ( n = 101), consistently across different cognitive scales; for example, an improvement in the ADAS cognitive subscale from baseline of -4.19 points (95% confidence interval = -5.74 to -2.63), which declined at 24 weeks of follow-up after the GEPT withdrawal.…”
Section: Herbal Formulations or Mixtures Of Herbal Ingredientsmentioning
confidence: 99%
“…This opens the possibility of the use of mimetic A -like peptides to induce NEP expression. Other types of pharmacologic induction are also being explored [116][117][118]. These studies outline the various strategies by which NEP augmentation can be developed therapeutically.…”
Section: Neprilysin Therapymentioning
confidence: 99%